A study on the effectiveness of the utilization of gondola ends at Gents and Sports Department Giant Cash and Carry Subang / Azamimah Muhadi - Muhadi, Azamimah (1998)
This is a study on gondola end and its effectiveness of utilizing it in retail institution. Basically not so many people know what gondola end is. Therefore it is the researcher obligation to deliver the information so that people are familiar with this term. This study is conducted to seek any weakness regarding Gents and Sports Department (G&S) at Giant Cash and Carry Subang. After several consideration! it is found that besides normal shelf, gondola end is playing its own roles in increasing the sales of G8S itself.